2020
DOI: 10.1016/j.amjoto.2020.102738
|View full text |Cite
|
Sign up to set email alerts
|

What is the best treatment option for head and neck cancers in COVID-19 pandemic? A rapid review

Abstract: With the onset of the COVID-19 crisis in late 2019, the health care systems of different countries are experiencing stressful conditions. Many patients need care in hospital wards and intensive care units (ICU). Head & neck cancers (HNC) are in a special condition in this pandemic. The main treatment in these patients is surgery. Most of these patients need care in the ICU, which is reduced in capacity in pandemic conditions. It's important to note that delays in the surgery of these patients make them non-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Surgery is the main course of treatment for most HNCs, and after the outbreak, waiting lists were inevitably prolonged as a result of reallocation of anesthesiologists and reassignment of intensive care units (ICUs) into COVID-19 wards for treatment of the most severe COVID 19 cases. As a result, the delay in diagnosis and treatment could lead to more aggressive surgical procedures, with increasing morbidity and increased risk of recurrence, or to a tumor shift to a non-resectable disease, with an associated increase in mortality [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is the main course of treatment for most HNCs, and after the outbreak, waiting lists were inevitably prolonged as a result of reallocation of anesthesiologists and reassignment of intensive care units (ICUs) into COVID-19 wards for treatment of the most severe COVID 19 cases. As a result, the delay in diagnosis and treatment could lead to more aggressive surgical procedures, with increasing morbidity and increased risk of recurrence, or to a tumor shift to a non-resectable disease, with an associated increase in mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…In most HNC cases, early diagnosis represents the boundary between less and more aggressive surgery, or between resectability and non-resectability of the disease, with a consequent increase in morbidity and mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…33,35 However, this strategy may have caused some drawbacks, because it has been found that patients with cancer contracting SARS-CoV-2 may have worse oncologic outcomes due to both a possible delay of treatments while waiting to become seronegative and a worsening of the patients' already fragile Performance Status. 32,36,37 The prevalence of COVID-19 among patients with cancer is unclear. Lai et al reported that 1% of patients with COVID-19 had a history of cancer, 36 whereas Yu et al estimated an 0.79% infection rate of SARS-CoV-2 in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the review on otorhinolaryngology/head and neck surgery (ORL-HNS) practice during the COVID-19 pandemic recently published in this journal by Salari [ 1 ]. We would like to share our current protocol for organizing ORL-HNS patient care in Germany (updated in December 2020) ( Fig.…”
mentioning
confidence: 99%